Species composition and diversity of fishes from the seagrass habitat of Lawas, Sarawak, Malaysia - I., Johan; M. K., Abu Hena; Idris, M. H.; S. M. N. Amin; A. Denil, N.; Kumar, U.; Karim, N. U. (Triveni Publishers, 2020)
Aim: To investigate the species composition and diversity of fishes from the seagrass habitat in Lawas, Sarawak, Malaysia. Methodology: Fishes were collected with an encircling gillnet net during the dry, wet and intermediate season of the year. Water characteristics were analyzed in-situ through analytical methods. Results: A total of 60 fish species from 37 families were recorded in the seagrass ecosystem. Dominant species with highest total abundance observed were Lethrinus lentjan (12.83%), Hyporhamphus limbatus (8.50%) and Leiognathus equulus (8.33%). Cluster analysis revealed three fish species assemblages; Lethrinus lentjan and Lutjanus fulviflamma (dry season), Nibea soldadu, Platycephalus indicus and L. equulus (intermediate season), while Hyporhamphus limbatus, Gerres erythrourus, Thryssa hamiltonii, Gerres oyena, Sphyraena jello and Gnathanodon speciosus (wet-intermediate season). All indices (no. of species, diversity and evenness) showed an increasing trend from dry, wet to intermediate season. Interpretation: The seagrass ecosystem of Lawas harbours a rich and diverse group of fish communities indicating an important fishery resource habitat. The findings of this study provide baseline information on fish resources from this seagrass ecosystem, which will be useful for the conservation and management of its fish resources in the future.